(untitled) (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in Valsad district of Gujarat to ascertain the personal, socio-economic characteristics of dairy farmers and data were collected randomly from 240 dairy animal owners through personal interview with the help of structured interview schedule. The present study revealed that majority of the owners were belonged middle age group, literate, nuclear type of family with more number of children making big size family. Most of the respondents were from schedule tribe category having medium level of extension contacts and mass media exposure with membership in one organization. Only few of the respondents were landless categories. Majority of respondents had small herd size and they possessed agriculture and livestock as their livelihood.